Republic of Armenia : Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2019)
This detailed assessment of observance has been conducted against the standard issued by the Basel Committee on Banking Supervision in 2012. The report also highlights that the Central Bank of Armenia has made significant progress in its approach to banking supervision with adoption of the risk-based program (RBS) framework and addressing gaps in the regulatory framework identified in the 2012 Basel Core Principles assessment. Improvements have been made in the regulatory regime regarding requirements for risk management, stress testing, corporate governance, country risk and consolidated supervision. Although the supervisory regime has recently transitioned from a rules-based to an RBS, there is a need for continued refinement of the program for more granular assessments of firms' capital needs. The process for conducting risk assessments of each firm has identified a need for building a stronger and more structured (system-wide) understanding of the level and magnitude of risk and the risk management capabilities across banking firms.